Analysis of p73 and p53 gene deletions in multiple myeloma - Schultheis, Beate; Krämer, Alwin; Willer, Andreas; Hegenbart, Ute; Goldschmidt, Hartmut; Hehlmann, Rüdiger (Leukemia, 1999)
Recently, p73, a protein with structural and functional similarities to p53, an extensively studied tumor suppressor gene, has been cloned. After being mapped to the chromosomal region 1p35-1p36, it has been postulated to act as a tumor suppressor gene, too, as this region is altered in several human malignancies. Deletions of the short arm of chromosome 1 have frequently been described in multiple myeloma (MM) whereas structural abnormalities of the 17p13 region including p53 are rare events in this disease. Since it has been proposed that especially neoplasias lacking p53 alterations might show a loss of heterozygosity at 1p35-1p36, we studied the frequency of p53 and p73 deletions in bone marrow mononuclear cells of 68 patients with MM, two patients with monoclonal gammopathy of undetermined significance and four patients with plasma cell leukemia. Dual-color fluorescence in situ hybridization (FISH) for p53 and p73 was performed using commercially available DNA probes for 17p13.3 and the microsatellite marker D1Z2, respectively. Centromeric DNA probes served to distinguish gene deletions from whole chromosome losses. In contrast to recently published FISH results, we only detected heterozygous p53 deletions in eight out of the 74 patients, three of them showing a monosomy 17. Heterozygous deletions of the D1Z2 region at 1p36 were found in six cases with one patient having a monosomy 1. Neither homozygous deletions of either chromosomal region nor nullisomies 1 or 17 could be detected. These results argue against a major role of p73 deletions in MM. As MM patients with 1p structural abnormalities have a significantly poorer survival rate than those with normal karyotypes, the role of other putative tumor suppressor genes located at the chromosomal region 1p36 in the pathogenesis of MM has to be determined.